Nickel-Cobalt Layered Double Hydroxide Nanosheets for High-performance Supercapacitor Electrode Materials - Chen, Hao; Hu, Linfeng; Chen, Min; Yan, Yan; Wu, Limin (Advanced functional materials, 2014)
A facile and novel one‐step method of growing nickel‐cobalt layered double hydroxide (Ni‐Co LDH) hybrid films with ultrathin nanosheets and porous nanostructures on nickel foam is presented using cetyltrimethylammonium bromide as nanostructure growth assisting agent but without any adscititious alkali sources and oxidants. As pseudocapacitors, the as‐obtained Ni‐Co LDH hybrid film‐based electrodes display a significantly enhanced specific capacitance (2682 F g−1 at 3 A g−1, based on active materials) and energy density (77.3 Wh kg−1 at 623 W kg−1), compared to most previously reported electrodes based on nickel‐cobalt oxides/hydroxides. Moreover, the asymmetric supercapacitor, with the Ni‐Co LDH hybrid film as the positive electrode material and porous freeze‐dried reduced graphene oxide (RGO) as the negative electrode material, exhibits an ultrahigh energy density (188 Wh kg−1) at an average power density of 1499 W kg−1 based on the mass of active material, which greatly exceeds the energy densities of most previously reported nickel or cobalt oxide/hydroxide‐based asymmetric supercapacitors. Ni–Co LDH electrode materials with ultrahigh capacitive performance are prepared. The capacitive performances of as‐obtained Ni–Co LDHs for pseudocapacitors and asymmetric supercapacitors significantly exceed those of most similar reported materials. This synthesis method can also be extended to synthesize other bimetallic LDHs with high electrochemical activity.